KNOWLEDGE AND AWARENESS LEVEL TOWARD INITIAL MANAGEMENT OF POISONING AMONG SAUDI POPULATION (CAHIERS MAGELLANES-NS, 2024)
Background: According to WHO, Poison is described as a substance or object, whether natural or artificial, that has the potential to be harmful to living organisms. Accidental poisoning is a major international issue. It is expected to remain one of the most common medical emergencies that doctors and medical facilities deal with at any moment. Consequently, this resulted in greater morbidity and mortality rates among almost a million people per year. Therefore, there is limited study in the literature regarding the knowledge and awareness of poisoning management in the Kingdom of Saudi Arabia.Objectives: This study aims to assess the knowledge and awareness level of poisoning management among Saudi population.Method: This is a cross-sectional study. The inclusion criteria include Citizens who live in Saudi Arabia and Adult males and females older than 18 who can complete the questionnaire during the period of 2023-2024. The exclusion criteria are adult males and females outside Saudi Arabia and Anyone who does not complete the questionnaire. With a 95% confidence level, an estimated sample size of 385 was calculated using the Qualtrics calculator.Results: The study included 416 participants, 54.8% of them were males. 48.6% of the participants possess a good knowledge level, 41.8% exhibits a moderate knowledge level, and 9.6% of the sample exhibit a weak knowledge level. Participants’ knowledge scores were significantly associated with both age and gender.Conclusion: In conclusion, Saudi general population exhibited a poor knowledge towards initial management of poisoning. By addressing education, access to information, cultural factors, and targeted interventions, it is possible to improve the knowledge and awareness level and ultimately reduce the burden of poisoning in Saudi Arabia.